Facility Management using digital Obeya Room by integrating BIM-Lean approaches – an empirical study - Nascimento, Daniel Luiz de Mattos; Quelhas, Osvaldo Luiz Gonçalves; Meiriño, Marcelo Jasmim; Caiado, Rodrigo Goyannes Gusmão; Barbosa, Simone D. J.; Ivson, Paulo (Journal of Civil Engineering and Management, 2018)
This paper applies a methodology for interdisciplinary Facilities Management (FM) by alingment between Building Information Modeling (BIM) and Lean. Initially, the literature review of BIM, FM and Lean principles. Afterwards, the research applies the Digital Obeya Room for improved FM and describes its application on a real-world case study. Lastly, the work presents a survey with specialists to assess the relevance of each BIM-Lean concepts and correlate their perceptions with the empirical results. The main collaborations of this work are: a conceptual framework that relates the PDCA (Plan-Do-Check-Act) cycle with BIM-Lean approaches; the identification of the most relevant BIM functionalies and Lean principles; and the real-world application of the framework procedures on FM.